Design and analysis of a low crosstalk error nested structure two-dimensional micro-displacement stage. (April 2021) - Jin, Tao; Luo, Siwei; Le, Yanfen; Wu, Junjie; Lei, Lihua; Zhang, Bo
In order to solve the low coupling displacement and high crosstalk error of multi-dimensional micro-displacement stage, a two-dimensional micro-displacement stage based on flexure hinges and piezoelectric ceramics is designed and analyzed. The whole stage adopts a nested parallel structure. The design parameters of flexure hinges are calculated using Pseudo-rigid body model. Those parameters are confirmed by a simulation before manufacturing the stage. A double frequency laser interferometer is used for measuring the displacement and crosstalk error of the stage when it's driven. The experimental results show that the maximum crosstalk error of the two-dimensional displacement platform within full travel is 0.98%, the displacement coupling rate approaches 91.4%, and the remaining trajectory deviation caused by hysteresis asymmetry can be reduced to 0.79%.